Comparison of inhibition resistance among PCR reagents for detection and quantification of environmental DNA. Issue 4 (15th October 2019) - Uchii, Kimiko; Doi, Hideyuki; Okahashi, Teruyuki; Katano, Izumi; Yamanaka, Hiroki; Sakata, Masayuki K.; Minamoto, Toshifumi
Abstract: Background: Real‐time PCR has been widely employed in environmental DNA (eDNA) surveys to detect and quantify target species. The biggest obstacle in real‐time PCR based eDNA assays is the inhibition of PCR amplification that results in false‐negative detection and uncertainty of quantification. Aims: Here, we aimed to evaluate inhibition resistance of PCR reagents for detection and quantification of environmental DNA. Materials & Methods: We compared six commercial PCR reagents, including four inhibitor‐resistant reagents, for resistance to major PCR inhibitory substances, i.e., humic, fulvic, and tannic acids. Then, we selected three inhibitorresistant reagents to test for their resistance to multiple natural inhibitors using field eDNA samples collected from various habitats. Results: We found that each inhibitor‐resistant reagent had its advantage and disadvantage depending on which inhibitory substance was used. Similarly, the inhibitory effects caused by field samples differed among the three inhibitor‐resistant reagents, where none of the reagents consistently showed strong resistance to all field samples. Conclusion: Our results indicate that the selection of appropriate PCR reagent would greatly ease PCR inhibition, and consequently improve the estimation of species distribution by real‐time PCR‐based eDNA assays. Abstract : PCR inhibitory effects caused by field eDNA samples differed between PCR reagents in real‐time PCR. Selection of appropriate PCR reagents would greatly ease PCR inhibition and consequently improve the accuracy of eDNA‐based estimation.